Integracja treści literackich z różnymi metodami pracy z dziećmi przedszkolnymi. Tydzień z Koziołkiem Matołkiem = Integration of literary content with various methods of working with preschool children. A week with Koziołek Matołek - Kuligowska, Emilia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article presents how to carry out activities with preschool children in different age groups. It shows the integration of teaching content from various fields (math, science, language, art) based on a short story by Kornel Makuszyński, "120 przygód Koziołka Matołka" ("120 adventures of Koziołek Matołek").
Keywords: integracja treści nauczania; edukacja przedszkolna; multimedia w przedszkolu; "120 przygód Koziołka Matołka" ("120 adventures of Koziołek Matołek"); integration of teaching content; early education; multimedia in kindergarten